Force feedback control for active stabilization of synchronous whirl orbits in rotor systems with non-linear stiffness elements - Cole M. (2017)
Synchronous vibration in rotor systems having bearings, seals or other elements with non-linear stiffness characteristics is prone to amplitude jump when operating close to critical speeds as there may be two or more possible whirl responses for a given unbalance condition. This paper describes research on the use of active control methods for eliminating this potentially undesirable behavior. A control scheme based on direct feedback of rotor-stator interaction forces is considered. Modelbased conditions for stability of low amplitude whirl, derived using Lyapunov's direct method, are used as a basis for synthesizing controller gains. Subsidiary requirements for existence of a static feedback control law that can achieve stabilization are also explained. An experimental validation is undertaken on a flexible rotor test rig where non-linear rotorstator contact interaction can occur across a small radial clearance in one transverse plane. A single radial active magnetic bearing is used to apply control forces in a separate transverse plane. The experiments confirm the conditions under which static feedback of the measured interaction force can prevent degenerate whirl responses so that the low amplitude contact-free orbit is the only possible steady-state response. The gain synthesis method leads to controllers that are physically realizable and can eliminate amplitude jump over a range of running speeds. Copyright © 2010 by ASME.